MEANING OF THE ISMAIL TUNALI ART CRITIC - (:unkn) unknown (ANADOLU UNIV, 2020)
This article aims at developing judgements and interpretations of Ismail Tunali's work on art and criticism. Prof. Dr. Ismail Tunali is a thinker who has contributed to the intellectual development of theoretical art, who has written a lot of books about art criticism. He has provided important insights and in-depth information into the field of plastic art via his comments, evaluations and the literature he has put forward.
Keywords: Art; Aesthetic; Creative; Ismail Tunali